2021
DOI: 10.3389/fpsyg.2021.740644
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work-From-Home Human Resource Practices on the Performance of Online Teaching Faculty During Coronavirus Disease 2019

Abstract: The purpose of this study was to investigate the impact of work-from-home (WFH) human resource (HR) practices on the performance of faculty under the drastic circumstances of coronavirus disease 2019 (COVID-19). The population of the study included faculty members of the higher education institutions in Sialkot, Pakistan. The study filled the gap of scarce literature on the impact of various HR practices by HR officials while working from home during lockdown observed to reduce the spread of COVID-19. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…As faculty and students adapted to virtual learning, the unexpected overnight change caused enormous stress and burnout (Almaiah et al. , 2020; Baloran, 2020; Irshad et al. , 2021; Usman et al.…”
Section: Introductionmentioning
confidence: 99%
“…As faculty and students adapted to virtual learning, the unexpected overnight change caused enormous stress and burnout (Almaiah et al. , 2020; Baloran, 2020; Irshad et al. , 2021; Usman et al.…”
Section: Introductionmentioning
confidence: 99%
“…According to Galanti et al (2021), job performance is the result of a person's character attributes, level of effort, and assistance given to the business. Additionally, previous study by Irshad et al (2021) found that mastery objectives promote longterm learning whereas job performance goals encourage short-term learning. Job Performance is another term given out by (Popovici, 2021).…”
Section: Job Performancementioning
confidence: 89%
“…Proficiency is a Job Performance category that represents attitudes like putting others first, being supportive of others, and being helpful (Ray & Aranhal, 2021). On the other hand, adaptability showed a mindset that enables people to deal with changes that influence their responsibilities while still staying within its purview (Irshad et al, 2021). Last but not least, proactivity is a person's ability to "predict changes in working techniques or processes as circumstances dictate," enabling them to take preventative action (Galanti et al, 2021).…”
Section: Job Performancementioning
confidence: 99%
“…Interestingly, besides side effects like worsening presenteeism (Shimura, Yokoi, Ishibashi, Akatsuka, & Inoue, 2021 ) and increasing emotional exhaustion (Chong, Huang, & Chang, 2020 ), workers perceived more productivity during WFH (Zappalà, Toscano, & Topa, 2021 ), and it decreased psychological and physical stress responses (Shimura et al, 2021 ). Some research highlights that the effectiveness of WFH depends on leadership (Shockley, Allen, Dodd, & Waiwood, 2021 ) and managerial control policies (Hartner-Tiefenthaler et al, 2021 ; Irshad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%